P1011Cryptogenic stoke and asymptomatic atrial fibrillation in a real world population: a single centre, implantable loop recorder study. (18th June 2020) - Faustino, M; Di Stefano, V; Franciotti, R; Furia, N; Di Girolamo, E; Bonanni, L; Onofrj, M; De Angelis, M V
Abstract: Funding Acknowledgements: None Background: The incidence of atrial fibrillation (AF) in cryptogenic stroke (CS) patients has been studied in carefully controlled clinical trials, but real-world data are limited. Purpose: Aim of this study was to investigated the incidence of AF in clinical practice among CS patients with an implantable cardiac monitor (ICM) recommended (IIA) for AF detection. Methods: Patients with CS admitted to our Stroke Unit were included in the study. Patiens received an ICM and were monitored for up to 2 years for AF detection (in-hospital clinic and remote monitoring). All detected AF episodes (≥30 sec) were considered. Results: From March 2016 to March 2019, 58 patients (mean age 68 ±12 years, 67% male) received an ICM to detect AF after a CS.  No patients were lost during follow-up. AF was detected in 23 patients (40% overall; AF group mean age 72 ± 11 years; 65% male) after a mean time of 6 months from ICM implantation (ranging from 2 days up to 2 years) and 8 months after CS (ranging from 1 month up to 2 years). In these AF patients anticoagulant treatment was prescribed, and no further stroke was reported. Conclusions: AF episodes were detected via continuous monitoring with ICMs in 40% of implanted CS patients. AF after CS was asymptomatic and thus unlikely to be detected by strategies based on intermittent short-term recordings. Therefore, ICMs should be considered as part of daily practice in the evaluation of CS patients.